Certain Types of Iron Oxide Nanoparticles are Not Suited to Passively Target Inflammatory Cells that Infiltrate the Brain in Response to Stroke. Issue 5 (May 2013) - Harms, Christoph; Datwyler, Anna Lena; Wiekhorst, Frank; Trahms, Lutz; Lindquist, Randall; Schellenberger, Eyk; Mueller, Susanne; Schütz, Gunnar; Roohi, Farnoosh; Ide, Andreas; Füchtemeier, Martina; Gertz, Karen; et al.
Intravenous administration of iron oxide nanoparticles during the acute stage of experimental stroke can produce signal intensity changes in the ischemic region. This has been attributed, albeit controversially, to the infiltration of iron-laden blood-borne macrophages. The properties of nanoparticles that render them most suitable for phagocytosis is a matter of debate, as is the most relevant timepoint for administration. Both of these questions are examined in the present study. Imaging experiments were performed in mice with 30 minutes of middle cerebral artery occlusion (MCAO). Iron oxide nanoparticles with different charges and sizes were used, and mice received 300 μ mol Fe/kg intravenously: either superparamagnetic iron oxide nanoparticles (SPIOs), ultrasmall SPIOs, or very small SPIOs. The particles were administered 7 days before MCAO, at the time of reperfusion, or 72 hours after MCAO. Interestingly, there was no observable signal change in the ischemic brains that could be attributed to iron. Furthermore, no Prussian blue-positive cells were found in the brains or blood leukocytes, despite intense staining in the livers and spleens. This implies that the nanoparticles selected for this study are not phagocytosed by blood-borne leukocytes and do not enter the ischemic mouse brain.